THE SOCIAL NECESSITY AND PRACTICAL SITUATION OF DEVELOPING STUDENTS' COMMUNICATION CULTURE BASED ON AN INTEGRATIVE APPROACH IN A GLOBAL EDUCATIONAL ENVIRONMENT - Kobilova Hilola Makhmudjonovna (Bright Mind Publishing, 2025)
This article explores contemporary management strategies for enhancing competitiveness in private educational institutions. The research examines how modern management theories including strategic management, digital transformation, stakeholder engagement, and performance measurement can be applied to improve private school operations and market positioning. The study identifies key areas where private schools can leverage modern management approaches to differentiate themselves in an increasingly competitive educational landscape. Through analysis of current management practices and emerging trends, this article provides a framework for private school administrators to enhance organizational effectiveness, improve educational outcomes, and maintain sustainable competitive advantages. The findings suggest that integration of technology-driven solutions, data-informed decision making, and stakeholder-centered approaches are essential for private school success in the contemporary educational environment.
Keywords: Private school management, educational competitiveness, strategic management, digital transformation, stakeholder engagement, performance measurement, educational leadership, competitive advantage.